Sovereign credit ratings and financial markets linkages: application to European data - António Afonso; Davide Furceri; Pedro Gomes (European Central Bank (ECB), 2011)
We use EU sovereign bond yield and CDS spreads daily data to carry out an event study analysis on the reaction of government yield spreads before and after announcements from rating agencies (Standard & Poor's, Moody's, Fitch). Our results show: significant responses of government bond yield spreads to changes in rating notations and outlook, particularly in the case of negative announcements; announcements are not anticipated at 1-2 months horizon but there is bi-directional causality between ratings and spreads within 1-2 weeks; spillover effects especially from lower rated countries to higher rated countries; and persistence effects for recently downgraded countries.
Keywords: C23; E44; G15; 330; credit ratings; rating agencies; sovereign yields